MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA LAPBOOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Sekar Kinasih, Ontya; Virdinarti Putra, Lisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine and analyze the effect of the Jigsaw cooperative learning model assisted by lapbook media on students' problem-solving skills. This research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The population of this study consisted of all fifth-grade students of SDN Langensari 04, Semarang Regency. The sample included an experimental class that received instruction through the Jigsaw cooperative learning model assisted by lapbook media and a control class that received conventional learning. Data were collected through problem-solving skill tests administered before (pretest) and after (posttest) the treatment. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing. The results showed that there was a significant difference in problem-solving skills between students in the experimental class and those in the control class. Students who learned through the Jigsaw cooperative learning model assisted by lapbook media demonstrated a higher improvement in problem-solving skills compared to students who experienced conventional learning. Therefore, it can be concluded that the Jigsaw cooperative learning model assisted by lapbook media has a significant effect on students' problem-solving skills. This learning model can serve as an effective alternative for enhancing students' problem-solving abilities through active participation in the learning process.